STRUCTURAL TRANSFORMATIONS IN THE METAL OF TRAIN WHEELS FROM THE ENGAGEMENT WITH THE RAIL - Vakulenko, I. O.; Gryshchenko, M. M. (Science and Transport Progress, 2008)
The destruction occurrence in a railroad wheel is caused by formation of the high local stresses produced by the inhomogeneous plastic deformation when the cyclic temperature change takes place during and after braking using brake shoes.